Parents’ mediation and a child’s agency: A transnational sojourner family’s online and offline language socialization - Artanti Puspita Sari (Indonesian Journal of Applied Linguistics, 2022)
Parents of transnational sojourner families, who stay temporarily in a country other than their own, navigate across online and offline spaces to mediate their children’s socialization into the linguistic competence they need for both contexts, namely the host country and the homeland. Simultaneously, their children establish agency in developing their own linguistic competence. However, language socialization studies have rarely examined the interconnection between parents’ mediation and children’s agency across both online and offline spaces of socialization. In this light, this study presents an ethnographic study that examined parents’ mediation and a child’s agency in the online and offline language socialization of an Indonesian-Muslim transnational sojourner family in the United States, which is underexplored in language research.  Additionally, using Darvin and Norton’s (2015) investment model, it explored how the family’s identities, ideologies, and capital structured the child’s language socialization.  Data were collected from observations, interviews, and artifacts that depict language practices within the family.  In-depth thematic analysis through triangulation of the various forms of data was conducted to obtain trustworthiness.  The findings demonstrated that parents’ mediation and their child’s agency across online and offline spaces contributed to the development of the child’s linguistic and multimodal repertoires while also strengthening the family’s local and cross-border connections. The findings also demonstrated competing priorities in identity as well as in social and cultural capital investment, which were eventually resolved. The study provides a deeper understanding of transnational sojourners’ language investment in their imagined communities, which span across the host and the home countries.